Case Report: Reduction in post-amputation phantom limb pain intensity accompanying the onset of phantom limb telescoping - Aternali, Andrea; Lumsden-Ruegg, Heather; Appel, Lora; Hitzig, Sander L.; Mayo, Amanda L.; Katz, Joel (Frontiers in Pain Research, 2024)
IntroductionIndividuals with limb loss frequently report post-amputation phenomena, including nonpainful phantom sensations, phantom limb pain (PLP), and residual limb pain (RLP). Although post-amputation pain is common, not all patients benefit from widely accepted treatments. A greater understanding of phantom limb “telescoping”, the experience of one's phantom hand or foot gradually approaching the residual limb, may assist in developing more effective interventions for reducing post-amputation pain. This case report explores the relationships between PLP, RLP, telescoping, and psychosocial experience in one person with a lower limb amputation. The aim of this case is to illustrate one possible relationship between telescoping and PLP as the mechanisms linking the two remain equivocal.MethodsThe participant is a 35-year-old male who underwent a transfemoral amputation due to a traumatic injury to his right leg approximately 4 years prior. He responded to questionnaires evaluating demographic and health-related information (e.g., age, sex, marital status, reason for amputation), pain and psychological variables via the Brief Pain Inventory (BPI-SF), ID Pain Questionnaire (IDPQ), Pain Catastrophizing Scale (PSC-4), Patient Health Questionnaire-4 (PHQ-4), Life Orientation Test-Revised (LOT-R), Connor-Davidson Resilience Scale (CD-RISC2), and Chronic Pain Acceptance Questionnaire (CPAQ-8) and telescoping, measured by a newly developed app. The participant completed a semi-structured interview that was designed to ascertain patterns in the overlapping experience of phantom limb telescoping and post-amputation pain.ResultsThe participant rated his average PLP as 10 on a Numeric Rating Scale (NRS) from 0 (“no pain”) to 10 (“worst pain imaginable”) shortly after amputation. Approximately 12 months later, the participant noticed a shortening of his phantom limb, with a concurrent decrease in PLP. At present, his average NRS pain intensity is a 5/10. The participant described how the daily, debilitating PLP intensity diminished to weekly, manageable pain over time. Most notably, his responses on questionnaires were consistent with neuropathic PLP, mild to moderate levels of pain interference, a high level of catastrophic thinking about pain, low optimism, and mild symptoms of anxiety and depression.DiscussionIn this report, telescoping appeared to be preceded by an initial reduction in PLP intensity but these findings are based on a single case report and must be replicated with a large sample size before we have a clearer idea of the relationship between telescoping and PLP. This study provides insight into factors that may maintain PLP, generating targets for further investigation.